Massive occurrence of benthic plastic debris at the abyssal seafloor beneath the Kuroshio Extension, the North West Pacific. (May 2021) - Nakajima, Ryota; Tsuchiya, Masashi; Yabuki, Akinori; Masuda, Shuhei; Kitahashi, Tomo; Nagano, Yuriko; Ikuta, Tetsuro; Isobe, Noriyuki; Nakata, Haruhiko; Ritchie, Heather; Oguri, Kazumasa; Osafune, Satoshi; et al.
Abstract: The abyss (3500–6500 m) covers the bulk of the deep ocean floor yet little is known about the extent of plastic debris on the abyssal seafloor. Using video imagery we undertook a quantitative assessment of the debris present on the abyssal seafloor (5700–5800 m depth) beneath the Kuroshio Extension current system in the Northwest Pacific. This body of water is one of the major transit pathways for the massive amounts of debris that are entering the North Pacific Ocean from Asia. Shallower sites (1400–1500 m depth) were also investigated for comparison. The dominant type of debris was single-use plastics - mainly bags and food packaging. The density of the plastic debris (mean 4561 items/km 2 ) in the abyssal zone was the highest recorded for an abyssal plain suggesting that the deep-sea basin in the Northwest Pacific is a significant reservoir of plastic debris. Highlights: Plastic debris is distributed ubiquitously and abundantly even at abyssal depths. Single-use plastics dominate the debris on the abyssal plains of the North Pacific. A 35-year-old food wrapper was found largely intact on the deep seafloor. The seafloor beneath the Kuroshio Extension is an important sink for plastic debris.